2014
DOI: 10.2337/db13-1872
|View full text |Cite
|
Sign up to set email alerts
|

Increased Interaction With Insulin Receptor Substrate 1, a Novel Abnormality in Insulin Resistance and Type 2 Diabetes

Abstract: Insulin receptor substrate 1 (IRS1) is a key mediator of insulin signal transduction. Perturbations involving IRS1 complexes may lead to the development of insulin resistance and type 2 diabetes (T2D). Surprisingly little is known about the proteins that interact with IRS1 in humans under health and disease conditions. We used a proteomic approach to assess IRS1 interaction partners in skeletal muscle from lean healthy control subjects (LCs), obese insulin-resistant nondiabetic control subjects (OCs), and part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 51 publications
0
51
0
Order By: Relevance
“…It is well known that insulin signaling is implicated in the regulation of adipocytes biology. Furthermore, an activation of phosphatidylinositol 3-kinase (PI3K) and protein kinase B (PKB)/Akt by the insulin/insulinlike growth factor 1 receptor (IRS1) protein appears to be important in the mechanism of glucose uptake in adipocytes (Rodrigues et al 2007, Caruso et al 2014. We observed a significant increased expression of miR-193a-3p, suggesting that, at least in EAT, this miRNA may be involved in the initial cellular responses to hyperglycemia (Kato et al 2009).…”
Section: Hyperglycemia (Rq)mentioning
confidence: 84%
“…It is well known that insulin signaling is implicated in the regulation of adipocytes biology. Furthermore, an activation of phosphatidylinositol 3-kinase (PI3K) and protein kinase B (PKB)/Akt by the insulin/insulinlike growth factor 1 receptor (IRS1) protein appears to be important in the mechanism of glucose uptake in adipocytes (Rodrigues et al 2007, Caruso et al 2014. We observed a significant increased expression of miR-193a-3p, suggesting that, at least in EAT, this miRNA may be involved in the initial cellular responses to hyperglycemia (Kato et al 2009).…”
Section: Hyperglycemia (Rq)mentioning
confidence: 84%
“…Immune-precipitates of IRS1 from homogenates of muscle from biopsies of glucose-tolerant lean, glucose-tolerant obese, and type 2 diabetic patients revealed 122 IRS-1 interacting proteins (81). Of these, PI3K α and β subunits showed an insulin-dependent increased association with IRS1 in muscle of lean but not that of the obese or type 2 diabetic subjects.…”
Section: Insulin Signalingmentioning
confidence: 98%
“…Bead eluates were resolved by 4–15% SDS-PAGE. For each lane, five slices (250–150 kDa, 150–75 kDa, 75–50 kDa, 50–25 kDa, and 25–10 kDa) were excised and subjected to in-gel trypsin digestion, peptide purification and HPLC-ESI-MS/MS analysis using an LTQ Orbitrap Elite as described[11]. Peptide/protein identification and quantification were performed using the MaxQuant, one of the popular quantitative proteomics software packages [18].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, PP2Ac was identified as an interaction partner of insulin receptor substrate-1 (IRS1) in murine HL-1 cardiomyocytes[10]. More recently, we have demonstrated that PP2Ac interacted with IRS1 in skeletal muscle of lean healthy controls, and this interaction is increased in insulin resistant obese nondiabetic controls and type 2 diabetic patients [11]. It is well established that chronic exposure of pancreatic β-cells to high glucose (HG; glucotoxicity) leads to metabolic dysfunction and demise [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation